2015
DOI: 10.1007/s11906-015-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and the Mineralocorticoid Receptor: Risk Factors for Cardiometabolic Disorders

Abstract: Preclinical studies have convincingly demonstrated a role for the mineralocorticoid receptor (MR) in adipose tissue physiology. These studies show that increased MR activation causes adipocyte dysfunction leading to decreased production of insulin-sensitizing products and increased production of inflammatory factors, creating an environment conducive to metabolic and cardiovascular disease. Accumulating data also suggest that MR activation may be an important link between obesity and metabolic syndrome. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 85 publications
(50 reference statements)
0
12
1
2
Order By: Relevance
“…It has also been reported that patients with primary aldosteronism have an increased incidence of IR that it is mediated by a diminished expression of genes involved in lipid metabolism in visceral adipose tissue compared to that of sex, age, and BMI-matched controls (49). Moreover, aldosterone has different effects on insulin metabolism, among others, interferes with insulin signaling pathways, reduces insulin receptor gene transcription and enhances degradation of insulin receptor substrates and is able to increase oxidative stress and inflammation (50).…”
Section: Discussionmentioning
confidence: 98%
“…It has also been reported that patients with primary aldosteronism have an increased incidence of IR that it is mediated by a diminished expression of genes involved in lipid metabolism in visceral adipose tissue compared to that of sex, age, and BMI-matched controls (49). Moreover, aldosterone has different effects on insulin metabolism, among others, interferes with insulin signaling pathways, reduces insulin receptor gene transcription and enhances degradation of insulin receptor substrates and is able to increase oxidative stress and inflammation (50).…”
Section: Discussionmentioning
confidence: 98%
“…Steroid hormones play important roles in the regulation of many physiological processes, including mineralocorticoid and glucose homeostasis or sexual differentiation [1][2][3]. Several steroids are linked to diseases such as obesity, obesity-induced hypertension and type 2 diabetes [4][5][6]. Adrenal glands and reproductive organs are the major sites of steroid hormone biosynthesis; cholesterol is the common precursor [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Other extrarenal tissue that express MR is the adipose tissue where MR is involved in essential processes such as differentiation, autophagy, and adipokine secretion [4,77]. MR expression is increased in adipose tissue of murine models of obesity and in obese human subjects, and different studies using MR antagonists and also adipocyte-specific MR transgenic mice have demonstrated a key role of MR in insulin signaling and inflammation, as reviewed previously [4, 77,78].…”
Section: Mr and Oxidative Stress In Adipose Tissuementioning
confidence: 99%